Gambaran Stres Akademik pada Mahasiswa yang Memiliki Celebrity Worship - Glaeny Chezya Avril Rompis; Agoes Dariyo (Lembaga Pengembangan Kinerja Dosen, 2026)
Academic stress is a condition of psychological strain that arises when academic demands are perceived to exceed an individual’s capacity to cope. In this context, university students frequently use entertainment related to public figures as an emotion-focused coping strategy, one of which is celebrity worship. This study aimed to describe the level of academic stress among students who engage in celebrity worship. A descriptive quantitative design was employed, with purposive sampling of 230 active university students aged 18–25 years. Data were collected using the Perception of Academic Stress Scale (PASS) and the Celebrity Attitude Scale (CAS). The results indicated that the respondents’ mean academic stress score was relatively high (M = 46.05; SD = 8.38), and the level of celebrity worship was also relatively high (M = 86.10; SD = 15.89). Categorization showed that most students were in the moderate academic stress category (47.0%), followed by high (30.0%) and low (23.0%). For celebrity worship, most respondents were categorized as moderate (49.6%), followed by high (29.6%) and low (20.9%). Crosstab analysis suggested an increasing proportion of high academic stress as celebrity worship levels increased; notably, the high celebrity worship category was dominated by high academic stress (67.6%). Group difference testing also revealed significant differences in academic stress by gender (p < 0.05), with female students tending to report higher stress levels. These findings indicate that celebrity worship may serve as an emotion-focused coping mechanism, yet it may also become a source of distraction when the attachment is excessive. The implications highlight the importance of fostering adaptive coping strategies and time management skills among students to manage academic stress more effectively.